BIBLIOMETRIC ANALYSIS AND SYSTEMATIC REVIEW FOR ENGINEERING CHANGE MANAGEMENT - Barroso, Paola Pimentel; de Andrade Júnior, Pedro Paulo (Brazilian Journal of Production Engineering, 2018)
This paper developed a bibliometric analysis followed by a systematic review on the topic engineering change management, which is the modification of product’s components after product entered mass production. A five-step methodology narrowed 33970 results to 62 documents highly relevant for developing a method for better control of engineering change management. A systematic review of those publications based on full reading and using System, Method and Out of Scope classification strategy allowed the identification of publications focused on Method and with core theme “change management” and “ECM control”. This resulted on 12 main relevant documents to compose a theoretical referential on engineering change management control study.